Characterization and immunoprotective efficacy of a fumarate reductase frdA mutant of Salmonella enteritidis - Zhu, Siping; Sun, Xinyi; Li, Hong; Su, Yongmei; Li, Chihuan; Zhu, Xintong; Ren, Chao; Liu, Xiaochen; Dong, Yulai; Shi, Qiumei; Zhang, Zhiqiang (Frontiers in Microbiology, 2025)
BackgroundSalmonella has the ability to adapt to variable environments by modulating metabolism. The Tricarboxylic Acid Cycle (TCA), as a core metabolic process, is critical for the environmental adaptation and infection process of Salmonella. Fumarate reductase FrdA is an important enzyme in the TCA cycle, mainly catalyzing the conversion of fumarate to succinate. But the association between this enzyme and the pathogenicity of Salmonella has not yet been reported.MethodsTo determine the role of fumarate reductase FrdA in Salmonella infection, a frdA-gene deletion strain of Salmonella enteritidis (S. enteritidis) was generated in this study, and the effect of frdA knockout on the biological properties and pathogenicity of S. enteritidis were further examined. Then, the immunoprotective effect of frdA-deficient strain was determined.ResultsThe results showed that frdA deletion did not affect the growth properties of S. enteritidis but caused a significant decreased survival under environmental stress, as well as a substantial decrease in its motility and biofilm formation ability. The ΔfrdA mutant displayed apparently reduced adhesion and invasion to Caco-2 cells and markedly impaired survival and replication in RAW264.7 cells. The animal infection test showed that the frdA gene deletion could lead to a significant decrease in virulence of S. enteritidis in mice, with a 64-fold increased LD50 for mice, and ΔfrdA demonstrated significantly decreased colonization in mouse tissues and organs. The transcriptomics results showed that frdA deletion resulted in altered expression of 2163 genes in S. enteritidis, and downregulated expression of csgD and other virulence genes were confimed by qPCR. Moreover, immunization of mice with the frdA deletion strain provided promising immune protection for mice.ConclusionFumarate reductase FrdA is closely associated with pathogenicity of S. enteritidis and that is an attractive candidate target for vaccine design of Salmonella.